The Relationship Between Work Motivation, Workload, and Job Satisfaction on the Performance of Permanent Employees RPSA at X Regional General Hospital Bogor Regency in 2024 - Maryani, Riza; Nina, Nina; Darmadja, Sobar (PROMOTOR, 2025)
Human resources function as the driving force of the hospital because the existence of the hospital depends on the HR involved behind it. To achieve the hospital's goals, HR with satisfactory performance is required. Research Objective: To determine the relationship between work motivation, workload, and job satisfaction on the performance of permanent employees RPSA at X Regional General Hospital Bogor Regency in 2024. The approach used in the data analysis of this research employs a quantitative approach using the Chi Square test. The motivation variable yielded a statistical test result with a p-value of 0.000 and an OR of 9.333 (95% CI= 3.338-26.101). The workload variable yielded a statistical test result with a p-value of 0.004 and an OR of 0.25 (95% CI= 101-653). The job satisfaction variable yielded a statistical test result with a p-value of 0.098. There is a relationship between work motivation and workload on the performance of permanent employees RPSA at X Regional General Hospital Bogor Regency, but the job satisfaction variable does not relate to the performance of permanent employees RPSA at X Regional General Hospital Bogor Regency.